A tumor within a tumor: gastric carcinomametastasizing to a uterine leiomyoma - Díaz del Arco, Cristina (2026)
Metastasis from one tumor to another is a rare clinical finding, as is the spread ofextragenital tumors to the female genital tract, with involvement of the uterine wall being particularly rare. This study presents a case of gastric carcinoma metastasis in a uterine leiomyoma, diagnosed after resection of the lesion due to hypermenorrhea.In addition, 39 previously described cases of extragenital metastases in leiomyomas are reviewed, in which the breast is the predominant origin (74.4%), followed by lung, skin, gastric, renal, and thyroid tumors. Despite the rarity of these cases, recognizing the possibility of extragenital metastases in uterine lesions is essential for guiding appropriate treatment and improving the patient's quality of life.